Breast Cancer Diagnosis Using K-means ‎Methodology (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
After lung cancer, breast cancer is the second cause of death among women. Due to the seriousness of the disease, research has stepped up to help diagnose this disease by providing medical personnel with a classification based computer systems that determine whether the patient is infected. This research focuses on the use method (K-means) for the diagnosis of breast cancer based on a global database known as (WBCD) dedicated to this purpose. The proposed method has proved its effectiveness in classification and the accuracy of the system is equal to 96.4861%.